Wear Characteristics of Circular cBN/Diamond Saws Produced by Hot Pressing - Islak, Serkan; Kir, Durmus; Celik, Halis (Carl Hanser Verlag, 2014)
This study describes the investigation of wear characteristics of circular cBN/diamond saws produced by hot pressing. In order to determine the usability of cBN instead of diamond, cBN and diamond grains were added to the bronze matrix. Production of the saws was performed at a sintering temperature of 600-700 degrees C for a sintering time of 3 minutes. Sawing tests were carried out to determine the wear characteristics of the saws by sawing natural stone. It is concluded that cBN together with diamond could be added to the matrix with a concentration of 12 ( the rest of concentration of 30 is diamond) and that the saws will have more wear if this concentration is exceeded. After sawing, SEM analyses of the saws indicate that there were more fractures and wear in cBN grains in comparison to the diamond grains. The results concluded that cBN can be used to saw softer natural stones, or can be added to the matrix together with diamond.
Keywords: Materials Testing; SEM analysis; cBN/diamond saws; Hot pressing; Wear